A review of commitment and implementation of sustainable development in higher education: results from a worldwide survey. (1st December 2015) - Lozano, Rodrigo; Ceulemans, Kim; Alonso-Almeida, Mar; Huisingh, Donald; Lozano, Francisco J.; Waas, Tom; Lambrechts, Wim; Lukman, Rebeka; Hugé, Jean
Abstract: During the last two decades, many higher education institutions have become involved in embedding sustainable development into their academic systems. The research for this paper was built upon discussions on declarations, charters, and other initiatives designed to commit their institutions to education for sustainable development. It analyses if such commitment leads to more sustainable development implementation within the academic institution. The research was performed using a survey, based upon a literature review of 60 peer-reviewed papers. The survey was divided into eight categories: background; institutional framework; campus operations; education; research; outreach and collaboration; on-campus experiences; and assessment and reporting. The survey was answered by 84 respondents from 70 institutions, worldwide. The responses were analysed via descriptive analysis, grounded theory, and inferential statistics. The results revealed that there were many examples of sustainable development implementation throughout the system; however, generally the efforts tended to be compartmentalised. The analyses also highlighted strong linkages between the institution's commitment to sustainability, implementation, and signing a declaration, charter, or initiative. The findings suggested that academic leadership's commitment was a leading cause for signing a declaration, charter, or initiative, and implementing sustainable development. The research team provided recommendations for higher educational leaders, including acknowledge that the higher education institution system is comprised of several inter-related elements; commit to sustainability by integrating it into policies and strategies; show the commitment by signing a declaration, charter, or initiative; establish short-, medium-, and long-term plans for its institutionalisation; and ensure that sustainable development is implemented throughout the system. Highlights: A literature review was done to explore SD implementation in HEIs. A survey was developed to explore SD commitment and implementation in practice. The survey was answered by respondents from 70 HEIs. The results showed strong links between SD commitment and implementation. Most SD efforts were not holistically integrated throughout the HEI system.